Southern youth : evoking Southern teenage identity through character design for animation : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design, College of Creative Arts, Massey University, Wellington, New Zealand - Mann, Rachel (Massey University, 2015)
In this project, I position myself as a New Zealand animator who designs characters that are appealing and which young New Zealand audiences aged 12-16 can relate to. Currently, 95.5% of Children’s Animation shown on New Zealand Television is made offshore and the characters depicted statistically and overwhelmingly white, heterosexual and male. The producers of this material are only slowly willing to change as they already dominate world market share with a set formulaic television structure that is economically profitable. I aim to counter this norm by designing appealing characters that are evocative of a particular group of New Zealand youth and the social and cultural issues they encounter growing up in regional New Zealand. Through case study analysis, content analysis, ethnographic study and design synthesis, I further aim to highlight the cultural diversity and teenage identity of one of New Zealand’s most sparsely populated regions – Southland.
Keywords: Cartoon characters; Design; Southland; New Zealand